Perbandingan Biaya Konstruksi Antara Metode Aktual Dan Value Engineering Pada Proyek Perumahan CV. Majas Di Banjarmasin: Comparison Of Construction Costs Between The Actual Method And Value Engineering In The Housing Project Of CV. Majas In Banjarmasin - Hazairin, Muhammad (Media Ilmiah Teknik Sipil, 2025)
Cost efficiency in small-scale housing projects remains a critical challenge in construction planning. This study introduces a novel integrative approach by combining a precision-based Pareto analysis with a multidimensional Value Index evaluation within the framework of Value Engineering (VE). A case study was conducted on a residential project by CV. Majas in Banjarmasin. Three dominant cost items—wall, concrete, and woodwork—were identified using a quantitative ΔC and ΔP formula, marking an advancement over conventional Pareto analysis. Alternative evaluations were based on five functional criteria: strength, weather resistance, aesthetics, ease of installation, and maintenance. Results indicate that VE implementation reduced total project costs by 3.08% without compromising quality or functionality. The most efficient alternatives included lightweight concrete blocks, ready-mix concrete K-225, and meranti wood. The key novelty lies in the measurable and function-oriented cost optimization model that combines quantitative cost classification with functional scoring, providing a more objective and applicable decision-making tool in construction cost management. These findings contribute to the development of more rational and replicable cost planning strategies for similar residential projects.